PERSEPSI STAKEHOLDER TERHADAP PEMBIAYAAN KESEHATAN KELUARGA MISKIN DENGAN KONSEP JAMINAN PEMELIHARAAN KESEHATAN DI KABUPATEN PARIGI MOUTONG PROVINSI SULAWESI TENGAH = STAKEHOLDERS PERCEPTION ABOUT HEALTH FUNDING ... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
Background: Health funding for poor families at Parigi Moutong District comes from oil compensation program priorities of health service fund which is directly given to community health centers and hospitals. The program is very benefici but its sustainability is being questioned because the funding can be used to provide health service for poor families for six months only. During the last two years. a program of health maintenance for poor families has been developed in some territories. Some initial findings show that the assignment to third party as program organizer has increased efficiency, effectiveness and local government commitment to health service and funding for poor families. Objectives: The study was meant to find out stakeholders' perception about health funding for poor families with health maintenance assurance. Methods: The study was of descriptive type which used case study design. The subjects of the study were stakeholders consisting of District Head, Head of Local Planning Council, Hospital director, Head of Community Health Center and leaders of the community. Data were collected through focus group discussion and in depth interview. Coding was then made to organize and analyze data for descriptive presentation. Result: Most of respondents considered that health funding for poor families with health maintenance assurance system was beneficial and greatly needed at Parigi Moutong District. Differentiation between program organizer and health service provider was expected to be more effective and efficient and could improve the farmer system. Source of funding according to respondents, should came from central government, local government and prosperous community through cross subsidy and private sector. Local government was very supportive to the program as seen from their readiness to issue an act or at least District Head's decree from the program to continue. Most of respondents suggested that local government should become program organizer which was non profit oriented. Most of respondents did not agree if PT. Askes functioned as program organizer because this did not go in line with the spirit of autonomy. Conclusion: Health funding for poor families with health maintenance assurance system was very beneficial and greatly needed as well as well supported by local government of Parigi Moutong District. Program organizer should be non profit oriented and managed by local government. Publicity should be made prior to program implementation. Keywords: perception, stakeholder, poor families, health assurance